Tata Kelola Koperasi dengan Pendekatan Stewardship atau Agency Theory - Sugiyanto Sugiyanto (J-Coop : Journal of Co-operative, 2025)
The good cooperative governance of most cooperatives in Indonesia still requires both theoretical and empirical study. Many cooperatives still do not enforce good governance principles, including the lack of annual member meetings, which demonstrate the accountability of management and supervisors to members. This study incorporates theoretical approaches, particularly those related to Stewardship Theory and Agency Theory to strengthen good cooperative governance. The results of the study indicate that, theoretically, cooperative governance can be approached using these two theories. The uniqueness of cooperative organizations should be managed using a stewardship approach, but in practice, conflicts of interest arise between boaard of director and members. Board of director has more information about the cooperative than members, and moral hazard exists. From this discussion, it can be concluded that good cooperative governance is based on conflicts of interest between members, board of directors, and supervisors.